Combined small-sided games and resistance training: Acute impact on physical capacity in young soccer players - Kusuma, Ketut Chandra Adinata; Artanayasa, I Wayan; Laksana, Anak Agung Ngurah Putra; Kusuma, I Dewa Made Aryananda Wijaya; Esaki, Kazuki (Journal Sport Area, 2025)
Background Problems: There are not many studies concerning a method combining resistance training (RT) and small-sided games (SSG) shortly on young soccer players. Research Objectives: This study reveals the acute impact of the combination of resistance training with small-sided games on the physical capacity of young soccer players. Methods: Quasi Experiment with a pretest-posttest group design, involving sixty students of Undiksha Soccer Student Activity Unit using a simple random sampling technique. Thirty samples each entered the combined group (SSG+RT), the small-sided games only (SSG) group, and all were involved in training four times a week (four weeks). Two sessions of aerobic endurance, agility, and leg muscle power (LMP) data collection were conducted in the field. Data were analysed using one-way MANOVA assisted by SPSS 16.0 with a significance level of 5%. Findings and Results: One-way MANOVA test showed F value = 61.390 and sig. value 0.000 (p < 0.05), which means there was a significant effect on aerobic endurance, agility, and LMP in both groups. There was no difference in aerobic endurance results in the SSG+RT and SSG groups with a sig. value of 0.092 (p > 0.05), but there was a difference in the two groups in agility with a sig. value of 0.000 (p < 0.05) and LMP with a sig. value of 0.000 (p < 0.05). Conclusion: To improve aerobic endurance, agility, and LMP simultaneously, a combined training method can be implemented, namely integrating resistance training into small-sided games. The current findings can help to improve the performance of young soccer players in a short time. However, it is necessary to study more deeply other variables that have the potential to affect the results of the current findings, such as longer training times.